Numerical Responses of Xylocoris flavipes (Reuter) (Hemiptera: Anthocoridae) on a Diet of Liposcelis decolor (Pearman) (Psocodea: Liposcelididae) - Augustine Bosomtwe; George Opit; Carla Goad; Kristopher Giles; Brad Kard (Insects)
Insect predators can suppress prey populations through increased progeny production. The present study investigated the numerical responses of adult♀ Xylocoris flavipes (Reuter) (Hemiptera: Anthocoridae) on a diet of Liposcelis decolor (Pearman) (Psocodea: Liposcelididae). Adult♀ X. flavipes were placed in arenas containing nymphs, adult females, or males of L. decolor at varying prey densities under laboratory conditions at 28 ± 1 °C, 63 ± 5 RH, and a 0:24 (L:D) photoperiod. The number of eggs laid by the predator was assessed at 24 h intervals for five days, and this was used to determine oviposition rate, oviposition efficiency, and efficiency of conversion of ingested food resources (ECI). This study showed that prey stage did not affect oviposition rate; however, there was a positive correlation between prey density and X. flavipes oviposition rate for all the prey stages. The predator’s oviposition efficiency and ECI (%) were inversely proportional to prey density for all prey stages. The current study shows that X. flavipes can produce more offspring on adults and nymphs of L. decolor when prey densities are high and can establish at low prey densities. Further evaluation of X. flavipes under field storage conditions is recommended to facilitate its incorporation into integrated management of psocids.